Cultivating REDD in Nepal’s Community Forestry: A Discourse for Capitalizing on Potential? - Dahal, Nagamindra; Banskota, Kamal (Journal of Forest and Livelihood, 2009)
This paper documents and analyses how REDD discoure is evolving in Nepal. The analysis shows that while there is consensus among stakeholders to respond to the unfolding opportunity of carbon financing through REDD, the discourse does not yet clarify the basis on which Nepal's community forestry has the potential to benefit from carbon financing. Despite good intentions, there is indequate understanding of the fundamental concept of REDD that is evolving internationally. There are a number of unsettled issues at international and national level. The potential of Nepal's community forestry to benefit from carbon financing depends on the ability of national stakeholders to resolve national issues collectively and work together to voice national interests internationally. Key words: REDD, R?PIN, community forestry, carbon trade, benefit?sharing Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.41-50